Election Governance Drafting a Special Voter List of Elections in 2019 in Indragiri Hulu Regency - Dedi Afda Putra; Bakaruddin Rosyidi; Tengku Rika Valentina (Universitas Muhammadiyah Ponorogo, 2022)
The preparation of the electoral register is a problem in every election. One of the problems that often arises in the form of the number of eligible voters but not registered in the list of permanent voters. This is evident in the large number of voters of resident identity card users who are registered in the special voter list. This research aims to analyze the problem of special voter list of the 2019 election in Indragiri Hulu Regency, Riau Province. In this study, researchers used an election governance perspective consisting of three stages, namely the stages of rule making, the implementation of rules, and the adjudication of rules. This research uses a qualitative approach with case study methods. The results showed that based on the perspective of election governance, the contributing factor to the large number of special voter lists for the 2019 election in Indragiri Hulu regency was at three stages of election governance. At the rule-making stage, in the form of implications of several policies taken by actors involved in the drafting of the rules. At the stage of implementation of the rules, in the form of the implementation of voter list preparation activities in Indragiri Hulu Regency which is not good. While the stage of adjudication rules in the form of non-accommodating recommendations of the Indragiri Hulu District Election Supervisory Agency related to special voters. There are two factors that are at the root of the problem of the large number of special voters. The root of the problem related to special voters who have not been registered on the Permanent Voter List, due to the non-implementation of matching and re-research of voters at the stage of updating the voter list. While the root of the problem related to special voters who have been registered on the permanent voter list, due to the difference in the maximum number of voters per polling place in elections and elections, so it must be re-mapping polling stations.